Effects of high temperature on photosynthesis and yield in mungbean (Bangladesh Journal of Botany, 2018)
Temperature (36°C) at pre-flowering stage of mungbean showed lower leaf conductance than others. Photosynthesis decreased but transpiration rate was not affected by the temperature treatments. Ambient temperature showed the highest yield. Yields at the temperature 36°C at pre-flowering, flowering and grain filling stages were identical.